Neuroactive Steroid Levels are Modified in Cerebrospinal Fluid and Plasma of Post‐Finasteride Patients Showing Persistent Sexual Side Effects and Anxious/Depressive Symptomatology. (24th July 2013) - Melcangi, Roberto Cosimo; Caruso, Donatella; Abbiati, Federico; Giatti, Silvia; Calabrese, Donato; Piazza, Fabrizio; Cavaletti, Guido
Abstract Introduction Observations performed in a subset of subjects treated with finasteride (an inhibitor of the enzyme 5α‐reductase) for male pattern hair loss seem to indicate that sexual dysfunction as well as anxious/depressive symptomatology may occur at the end of the treatment and continue after discontinuation. Aim A possible hypothesis to explain depression symptoms after finasteride treatment might be impairment in the levels of neuroactive steroids. Therefore, neuroactive steroid levels were evaluated in paired plasma and cerebrospinal fluid samples obtained from male patients who received finasteride for the treatment of androgenic alopecia and who, after drug discontinuation, still show long‐term sexual side effects as well as anxious/depressive symptomatology. Methods The levels of neuroactive steroids were evaluated by liquid chromatography–tandem mass spectrometry in three postfinasteride patients and compared to those of five healthy controls. Main Outcome Measures Neuroactive steroid levels in plasma and cerebrospinal fluid of postfinasteride patients and healthy controls. Results At the examination, the three postfinasteride patients reported muscular stiffness, cramps, tremors, and chronic fatigue in the absence of clinical evidence of any muscular disorder or strength reduction. Severity and frequency of the anxious/depressive symptoms were quite variable; overall, all the subjects had a fairly complex and constant neuropsychiatric pattern. Assessment of neuroactive steroid levels in patients showed some interindividual differences. However, the most important finding was the comparison of their neuroactive steroid levels with those of healthy controls. Indeed, decreased levels of tetrahydroprogesterone, isopregnanolone and dihydrotestosterone and increased levels of testosterone and 17β‐estradiol were reported in cerebrospinal fluid of postfinasteride patients. Moreover, decreased levels of dihydroprogesterone and increased levels of 5α‐androstane‐3α, 17β‐diol and 17β‐estradiol were observed in plasma. Conclusion The present observations confirm that an impairment of neuroactive steroid levels, associated with depression symptoms, is still present in androgenic alopecia patients treated with finasteride despite the discontinuation of the treatment. Melcangi RC, Caruso D, Abbiati F, Giatti S, Calabrese D, Piazza F, and Cavaletti G. Neuroactive steroid levels are modified in cerebrospinal fluid and plasma of postfinasteride patients showing persistent sexual side effects and anxious/depressive symptomatology. J Sex Med 2013;10:2598–2603.